#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-5470-145

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# Chapter 8: Linear Equations in One Variable Exercise – 8.1

### Question: 1

Verify by substitution that:

(i) x = 4 is the root of 3x – 5 = 7

(ii) x = 3 is the root of 5 + 3x = 14

(iii) x = 2 is the root of 3x – 2 = 8x – 12

(iv) x = 4 is the root of 3x/2 = 6

(v) y = 2 is the root of y – 3 = 2y – 5

(vi) x = 8 is the root of (1/2)x + 7 = 11

### Solution:

(i) x = 4 is the root of 3x - 5 = 7.

Now, substituting x = 4 in place of ‘x’ in the given equation 3x - 5 = 7,

3(4) – 5 = 7

12 – 5 = 7

7 = 7

Since, LHS = RHS

Hence, x = 4 is the root of 3x - 5 = 7.

(ii). x = 3 is the root of 5 + 3x = 14.

Now, substituting x = 3 in place of ‘x’ in the given equation 5 + 3x = 14,

5 + 3(3) = 14

5 + 9 = 14

14 = 14

Since, LHS = RHS

Hence, x = 3 is the root of 5 + 3x = 14.

(iii). x = 2 is the root of 3x – 2 = 8x – 12.

Now, substituting x = 2 in place of ‘x’ in the given equation 3x –2 = 8x – 12,

3(2) – 2 = 8(2) – 12

6 – 2 = 16 – 12

4 = 4

Since, LHS = RHS

Hence, x = 2 is the root of 3x – 2 = 8x – 12.

(iv) x = 4 is the root of 3x/2 = 6.

Now, substituting x = 4 in place of ‘x’ in the given equation 3x/2 = 6,

(3× 4)/2 = 6

12/2 = 6

6 = 6

Since, LHS = RHS

Hence, x = 4 is the root of 3x/2 = 6.

(v). y = 2 is the root of y – 3 = 2y – 5.

Now, substituting y = 2 in place of ‘y’ in the given equation y – 3 = 2y – 5,

2 – 3 = 2(2) – 5

-1 = 4 – 5

-1 = -1

Since, LHS = RHS

Hence, y = 2 is the root of y – 3 = 2y – 5.

(vi). x = 8 is the root of 12x + 7 = 11.

Now, substituting x = 8 in place of ‘x’ in the given equation 12x + 7 = 11,

12(8) + 7 =11

4 + 7 = 11

11 = 11

Since, LHS = RHS

Hence, x = 8 is the root of 12x + 7 = 11.

### Question: 2

Solve each of the following equations by trial and error method:

(i) x + 3 = 12

(ii) x – 7 = 10

(iii) 4x = 28

(iv) x/2 + 7 = 11

(v) 2x + 4 = 3x

(vi) x/4 = 12

(vii) 15/x = 3

(viii) x/18 = 20

### Solution:

(i) x + 3 = 12

Here, LHS = x + 3 and RHS = 12

 x LHS RHS Is LHS = RHS 1 1 + 3 = 4 12 No 2 2 + 3 = 5 12 No 3 3 + 3 = 6 12 No 4 4 + 3 = 7 12 No 5 5 + 3 = 8 12 No 6 6 + 3 = 9 12 No 7 7 + 3 = 10 12 No 8 8 + 3 = 11 12 No 9 9 + 3 = 12 12 Yes

Therefore, if x = 9, LHS = RHS.

Hence, x = 9 is the solution to this equation.

(ii) x – 7 = 10

Here, LHS = x – 7 and RHS = 10.

 x LHS RHS Is LHS = RHS 9 9 – 7 = 2 10 No 10 10 – 7 = 3 10 No 11 11 – 7 = 4 10 No 12 12 – 7 = 5 10 No 13 13 – 7 = 6 10 No 14 14 – 7 = 7 10 No 15 15 – 7 = 8 10 No 16 16 – 7 = 9 10 No 17 17 – 7 = 10 10 Yes

Therefore, if x = 17, LHS = RHS.

Hence, x = 17 is the solution to this equation.

(iii) 4x = 28

Here, LHS = 4x and RHS = 28.

 x LHS RHS Is LHS = RHS 1 4 x 1 = 4 28 No 2 4 x 2 = 8 28 No 3 4 x 3 = 12 28 No 4 4 x 4 = 16 28 No 5 4 x 5 = 20 28 No 6 4 x 6 = 24 28 No 7 4 x 7 = 28 28 Yes

Therefore, if x = 7, LHS = RHS

Hence, x = 7 is the solution to this equation.

(iv) x/2 + 7 = 11

Here, LHS = x/2 + 7 and RHS = 11.

Since RHS is a natural number, x/2 must also be a natural number, so we must substitute values of x that are multiples of 2.

 x LHS RHS Is LHS = RHS 2 2/2 + 7 = 8 11 No 4 4/2 + 7 = 9 11 No 6 6/2 + 7 = 10 11 No 8 8/2 + 7 = 11 11 Yes

Therefore, if x = 8, LHS = RHS.

Hence, x = 8 is the solution to this equation.

(v) 2x + 4 = 3x

Here, LHS = 2x + 4 and RHS = 3x.

 x LHS RHS Is LHS = RHS 1 2(1) + 4 = 6 3(1) = 3 No 2 2(2) + 4 = 8 3(2) = 6 No 3 2(3) + 4 =10 3(3) = 9 No 4 2(4) + 5 = 12 3(4) = 12 Yes

Therefore, if x = 4, LHS = RHS.

Hence, x = 4 is the solution to this equation.

(vi) x/4 = 12

Here, LHS = x/4 and RHS = 12.

Since RHS is a natural number, x/4 must also be a natural number, so we must substitute values of x that are multiples of 4.

 X LHS RHS Is LHS = RHS 16 16/4 = 4 12 No 20 20/4 = 5 12 No 24 24/4 = 6 12 No 28 28/4 = 7 12 No 32 32/4 = 8 12 No 36 36/4 = 9 12 No 40 40/4 = 10 12 No 44 44/4 = 11 12 No 48 48/4 = 12 12 Yes

Therefore, if x = 48, LHS = RHS.

Hence, x = 48 is the solution to this equation.

(vii) 15x = 3

Here, LHS = 15x and RHS = 3.

Since RHS is a natural number, 15x must also be a natural number, so we must substitute values of x that are factors of 15.

 x LHS RHS Is LHS = RHS 1 15/1= 15 3 No 3 15/3 = 5 3 No 5 15/5 = 3 3 Yes

Therefore, if x = 5, LHS = RHS.

Hence, x = 5 is the solution to this equation.

(viii) x/18 = 20

Here, LHS = x/18 and RHS = 20.

Since RHS is a natural number, x/18 must also be a natural number, so we must substitute values of x that are multiples of 18.

 X LHS RHS Is LHS = RHS 324 324/18 = 18 20 No 342 342/18 = 19 20 No 360 360/18 = 20 20 Yes

Therefore, if x = 360, LHS = RHS.

Hence, x = 360 is the solution to this equation.